Mapping and selection of criteria for comprehensive rehabilitation of mass housing neighborhoods. - Rico-Pinazo, Pablo; Márquez-Ballesteros, María José; Navas-Carrillo, Daniel (Universidad Politécnica de Cartagena, 2024)
This paper seeks to define a basic methodology aimed at identifying relevant mass housing ensembles within the city of Málaga whose regeneration is regarded as crucial. Housing ensembles are selected using a set of criteria based upon building age, height and ensemble size. To help determine intervention priority, two main indicators are proposed: dwelling gross floor area defect and number of dwelling types. The document concludes by stressing the need for a broader methodology that helps identifying intervention units in a glance using Geographical Information Systems and extensible to other cities, for which further research is required.
Keywords: Urbanismo; Barrios - Rehabilitación - Málaga; Urban regeneration; Mass housing; Climate crisis; Re-naturalization; Geographical information systems